Analisis Tingkat Pelayanan (Level of Service) pada Fasilitas Terminal Keberangkatan Internasional Bandar Udara I Gusti Ngurah Rai - Bali dalam Memfasilitasi Pertumbuhan Pergerakan Penumpang - Agatha Alventri Delvina Klau; Djoko Widagdo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the Level of Service (LoS) at the international departure terminal facilities at I Gusti Ngurah Rai Airport, Bali, in accommodating the growth of passenger traffic. Referring to IATA standards, PM 178 of 2015, and PM 41 of 2023, this research evaluates the performance of facilities such as passenger and baggage screening, check-in, immigration, and waiting areas. The research method used is qualitative, with data collected through observation, interviews, and documentation. The results show that the international departure terminal facilities meet the established service standards and are capable of handling passenger congestion during holiday seasons (high season and peak season). Efforts made by airport management include terminal expansion, queue management, and the enhancement of security systems with the latest technology. In conclusion, the Level of Service at I Gusti Ngurah Rai Airport is categorized as good and complies with existing standards, but infrastructure development is still needed to accommodate future increases in passenger numbers.